Global prospective case series of ERCPs using a single-use duodenoscope - Bruno, Marco J.; Beyna, Torsten; Carr-Locke, David; Chahal, Prabhleen; Costamagna, Guido; Devereaux, Benedict; Giovannini, Marc; Goenka, Mahesh K.; Khor, Christopher; Lau, James; May, Gary; Muthusamy, V. Raman; Patel, Sandeep; Petersen, Bret T.; Pleskow, Douglas K.; Raijman, Isaac; Reddy, D. Nageshwar; Repici, Alessandro; Ross, Andrew S.; Sejpal, Divyesh V.; Sherman, Stuart; Siddiqui, Uzma D.; Ziady, Christopher; Peetermans, Joyce A.; Rousseau, Matthew J.; Slivka, Adam; EXALT Single-use Duodenoscope Study Group (Endoscopy, 2023)
Background The first commercialized single-use duodenoscope was cleared by the US Food and Drug Administration in December 2019. Data regarding endoscopic retrograde cholangiopancreatography (ERCP) using a single-use duodenoscope are needed on a broader range of cases conducted by endoscopists with varying levels of experience in a wide range of geographic areas.Methods 61 endoscopists at 22 academic centers in 11 countries performed ERCP procedures in adult patients aged ≥ 18. Outcomes included ERCP completion for the intended indication, rate of crossover to a reusable endoscope, device performance ratings, and serious adverse events (SAEs).Results Among 551 patients, 236 (42.8 %) were aged > 65, 281 (51.0 %) were men, and 256 (46.5 %) had their procedure as an inpatient. ERCPs included 196 (35.6 %) with American Society for Gastrointestinal Endoscopy complexity of grades 3–4. A total of 529 ERCPs (96.0 %) were completed: 503 (91.3 %) using only the single-use duodenoscope, and 26 (4.7 %) with crossover to a reusable endoscope. There were 22 ERCPs (4.0 %) that were not completed, of which 11 (2.0 %) included a crossover and 11 (2.0 %) were aborted cases (no crossover). Median ERCP completion time was 24.0 minutes. Median overall satisfaction with the single-use duodenoscope was 8.0 (scale of 1 to 10 [best]). SAEs were reported in 43 patients (7.8 %), including 17 (3.1 %) who developed post-ERCP pancreatitis.Conclusions In academic medical centers over a wide geographic distribution, endoscopists with varying levels of experience using the first marketed single-use duodenoscope had good ERCP procedural success and reported high performance ratings for this device.